A Buffet of Deserts: An Examination of the Underlying Principles of Desert in Job - Zachary Alexander (Kairos (English Ed.))
Job challenges the theological milieu of retributive justice prevalent in Near- Eastern society by daring to ask the veritable question: can people deserve? This article examines the theories of desert, agency, and righteousness embedded within the Job manuscript. Bracketing the question of theodicy, this study utilizes contemporary philosophical, theological and exegetical considerations to examine what Job declares concerning the concept of Desert. This article uncovers a basic underlying Theory of Desert, which seems to correspond with the current compatibilist perspective in lieu of libertarianism or hard determinism. Though a basic moral desert finds a level of affirmation within the pages of Job, the book bears witness to the restricted nature of desert theories. Insofar as desert exists, God’s awesome power diminishes its significance. Human desert has boundaries and demands humility in light of the power and omnipotence of God. Humans are at once deserving, free, responsible agents and bounded, desert-less individuals without liberty before God.